1992
DOI: 10.1159/000154650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroid State on the Morphof unctional Properties of Heart Mitochondria

Abstract: For an evaluation of the effect of thyroid hormone on the mitochondrial compartment of heart, we have studied morphological and functional characteristics of mitochondria within the heart of rats in different thyroid states. In particular, the relationship between membrane-bound proteins, such as the cytochromes, and the surface of inner mitochondrial membranes has been investigated. By quantitative electron microscopy it has been shown, according to our previous data, that thyroidectomy causes an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…THs also regulate the synthesis of nuclear- as well as mitochondrial-encoded mitochondrial proteins via a nuclear mechanism [ 62 ]. Regardless of a decline in the number of mitochondria per cell in the hyperthyroid heart [ 63 ], there is a rise in respiratory chain proteins of the mitochondria [ 64 ]. These proteins can significantly contribute to the TH-provoked stimulation of mitochondrial respiration [ 59 , 64 ] and cause enhanced ROS generation [ 53 ].…”
Section: Sources Of Increased Oxidative Stress In the Hyperthyroidmentioning
confidence: 99%
See 1 more Smart Citation
“…THs also regulate the synthesis of nuclear- as well as mitochondrial-encoded mitochondrial proteins via a nuclear mechanism [ 62 ]. Regardless of a decline in the number of mitochondria per cell in the hyperthyroid heart [ 63 ], there is a rise in respiratory chain proteins of the mitochondria [ 64 ]. These proteins can significantly contribute to the TH-provoked stimulation of mitochondrial respiration [ 59 , 64 ] and cause enhanced ROS generation [ 53 ].…”
Section: Sources Of Increased Oxidative Stress In the Hyperthyroidmentioning
confidence: 99%
“…Regardless of a decline in the number of mitochondria per cell in the hyperthyroid heart [ 63 ], there is a rise in respiratory chain proteins of the mitochondria [ 64 ]. These proteins can significantly contribute to the TH-provoked stimulation of mitochondrial respiration [ 59 , 64 ] and cause enhanced ROS generation [ 53 ]. Effectively, Asayama et al reported increased mitochondrial oxidative metabolism in hypertrophied hyperthyroid rat hearts and proposed a key role for this observation in TH-induced myocardial dysfunction [ 25 , 43 , 44 ].…”
Section: Sources Of Increased Oxidative Stress In the Hyperthyroidmentioning
confidence: 99%